Metal-organic framework nanocomposites : from design to application - Khan, Anish (Boca Raton, FL : CRC Press, 2020)
"This book assembles the latest advances in MOF nanocomposites, emphasizing their design, characterization, manufacturing, and application, and offers a wide-ranging view of these materials with exceptional physical and chemical properties. The book discusses various types of MOF materials, such as polyaniline MOF nanocomposites, magnetic MOF nanocomposites, and carbon nanotube-based MOF nanocomposites. Chapters on the usage of these materials in pollutant removal, electrochemical devices, photocatalysts, biomedical applications, and other applications are also included"--
OCLC-licensed vendor bibliographic record.
Keywords: Nanocomposites (Materials); Metal-organic frameworks; TECHNOLOGY / Engineering / Chemical & Biochemical